Eksistensi FKUB dalam Memelihara Kerukunan Umat Beragama di Indonesia - Firdaus, Muhammad Anang (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2014)
Unitary Republic of Indonesia (NKRI) was a large country consisting of diverse ethnicity, culture, language, and religion. This diversity had the potential to cause conflict and division, included inter-religious conflict. In keeping the religious life in harmony and peace, the government issued ministerial decree of Religious and Home Affairs (PBM) No. 9 and 8 of 2006. The release of this PBM made birth of Harmony Forum (FKUB) at the province, city, and district. The existence of FKUB provided fresh air and a great opportunity for the realization of peace of religious communities in various regions in Indonesia. In fact, the performance in some areas FKUB showed mixed results. This was not out of the supporting factors and inhibiting factors of FKUB performance in each area.